The Constitutional Court's Decision on the Perppu on Mass Organizations from the Perspective of Rechtsstaat and Critical Legal Studies - Bimantara, Arya; Salman, Radian (JUSTISI, 2025)
This study aims to analyze the Constitutional Court's consistency in reviewing the constitutionality of Government Regulation in Lieu of Law (Perppu) No. 2 of 2017 concerning Mass Organizations, which was later ratified as Law No. 16 of 2017. The study focuses on two main issues: first, whether the issuance of the Perppu meets the criteria of "compelling urgency" as defined in Decision No. 138/PUU-VII/2009; second, how the Court interprets multi-interpretable phrases such as "contrary to Pancasila" and "threatening national stability," for restricting the right to associate. The method used is normative legal research with a statute, case (ratio decidendi), and conceptual approaches, examining the principles of lex certa, due process, proportionality, and contrarius actus, strengthened by critical legal studies (CLS) to uncover the political legal dimensions behind the Constitutional Court's jurisprudence. The novelty of this research lies in its emphasis on the Constitutional Court's tendency to provide formal validation for the formation of Perppu but its absence in providing substantive interpretation of crucial clauses subject to multiple interpretations, combining legal-dogmatic analysis and CLS to assess the consistency of the Constitutional Court's decision on the Perppu on Mass Organizations, something that has not been done in previous studies which tend to discuss procedural or human rights aspects partially. The results indicate that the Court prioritizes political stability over human rights protection, thus creating a double standard in the application of the rule of law principler. In conclusion confirms although the Constitutional Court affirmed the constitutionality of the Perppu and the Mass Organizations Law, a passive attitude towards the multi-interpretable clauses opens up space for the normalization of restrictions on the right to associate outside the principles of legality, necessity, and proportionality as required by the ICCPR.